Heme accumulation in endothelial cells impairs angiogenesis by triggering paraptosis - Petrillo, Sara; Vinchi, Francesca (Cell death and differentiation, 2017)
Heme is required for cell respiration and survival. Nevertheless, its intracellular levels need to be finely regulated to avoid heme excess, which may catalyze the production of reactive oxygen species (ROS) and promote cell death. Here, we show that alteration of heme homeostasis in endothelial cells due to the loss of the heme exporter FLVCR1a, results in impaired angiogenesis. In vitro, FLVCR1a silencing in endothelial cells causes defective tubulogenesis and poor viability due to intracellular heme accumulation. Consistently, endothelial-specific Flvcr1a knockout mice show aberrant angiogenesis responsible for hemorrhages and embryonic lethality. Importantly, we demonstrate that impaired heme export leads to endothelial cell death by paraptosis and provide evidence that endoplasmic reticulum (ER) stress precedes heme-induced paraptosis. These findings highlight a crucial role for the cytosolic heme pool in the control of endothelial cell survival and in the regulation of the angiogenic process. Interfering with endothelial heme export represents a valuable model for a deeper understanding of the molecular mechanisms underlying heme-triggered paraptosis and, in the future, might provide a novel tool for the modulation of angiogenesis in pathophysiologic conditions.